A DISSENT TO THE GENERAL PRICE-LEVEL ADJUSTMENT PROPOSAL. - Tracy, John A. (The Accounting Review, 1965)
Abstract This paper is an attempt to discredit the general price-level adjustment proposal on theoretical grounds. It is argued below that general price-level adjustments are inconsistent with the nature of the business enterprise and the function of financial statements of the business enterprise. They are used to measure the comparative value of the monetary unit at different dates. A dollar at one date may be a larger or smaller percent of a dollar at another date in terms of value represented. The same value at two points in time may cost different amounts of money. For example, $1.00 one year ago is the value equivalent of $1.05 today if the general level of prices has increased live percent during the year. The essence of the general price-level adjustment process is to restate the $1.00 entry of one year ago to $1.05. In this manner the chronological series of original dollar amount entries to the accounts of the firm are converted into value quantities of a unit equal to the current value-size of one dollar. Most explanations for this serious breach between accounting theory and accounting practice stress the many practical problems of making and reporting general price-level adjustments.